Echocardiographic assessment of left ventricular function after COVID-19 vaccination in adults - Hala Ahmed Mohamed Ahmed Wahdan; Reda Biomy Bastwisy; Wael Anwer Haseeb (Journal of the Pakistan Medical Association, 2023)
Objectives: To assess left ventricular function by conventional and speckle tracking echocardiography in subjects having received coronavirus disease-2019 vaccine. Method: The cohort study was conducted from April 2021 to April 2022 at the Department of Cardiology, Kafrelsheikh University Hospital, Egypt, and comprised adults of either gender who had received coronavirus disease-2019 vaccine. Detailed history was noted before clinical assessment, electrocardiogram and echocardiography, which were done at baseline and after two weeks of the last vaccine dose. Apical 4, apical 3 and apical 2 strains were obtained to get the global longitudinal strain. Data was analysed using SPSS 20. Results: Of the 100 subjects, 50(50%) each were males and females. The overall mean age was 39.20±14.57 years. There were 16(16%) subjects with diabetes mellitus and 21(21%) with hypertension. Regarding vaccine distribution, 34(34%) had received AstraZeneca AZD1222, 31(31%) had BioNTech Pfizer vaccine BNT162B2 and 35(35%) had Sinopharm Beijing Institute of Biological Products BBIBP-CorV. The global longitudinal strain before and after vaccination did not show a significant difference (p<0.063). There was no significant variation in global longitudinal strain between the various vaccination types (p=0.584). Conclusion: The studied vaccines had similarly acceptable safety profiles regarding left ventricular functions. Keywords: COVID-19, Myocarditis, Echocardiography, Electrocardiography, Myocardial Infarction, Cardiology.